Liquid worm-like and proto-micelles: water solubilization in amphiphile–oil solutions. Issue 18 (27th April 2018) - Qiao, Baofu; Littrell, Kenneth C.; Ellis, Ross J.
Abstract : Weak noncovalent interactions control water dispersion and solubility in oil. Abstract : Noncovalent interactions determine the structure–property relationship of materials. Self-assembly originating from weak noncovalent interactions represents a broad variety of solution-based transformations spanning micellization and crystallization, which, nevertheless, conforms to neither colloid nor solution sciences. Here, we investigate the weak self-assembly in water–amphiphile–oil solutions to understand the connection between the amphiphilic molecular structure and water solubilization in oil. X-ray and neutron scattering, converged with large-scale atomistic molecular dynamics simulations, support the fact that the amphiphiles assemble into liquid worm-like micelles and loose inverted proto-micelles. The inverted proto-micelles are energetically ready to accommodate a higher amount of water. These structures arise from a balance of intermolecular interactions controlled by the amphiphile tail-group structures. Thus, by linking the aggregate morphology to the molecular structure, this work provides insights on the molecular design for control of water solubility and dispersion in oil.